Triarchic Model Traits as Predictors of Bullying and Cyberbullying in Adolescence - Baroncelli, Andrea (Journal of interpersonal violence, 2022)
The triarchic model of psychopathy includes a disinhibition dimension related to externalizing outcomes, a meanness dimension pertaining to callous-unemotional traits, and a boldness dimension referring to emotional stability and high confidence in peer relationships. Some dimensions of psychopathy have been extensively investigated in samples of children and adolescents; in particular, the callous-unemotional (meanness) dimension has been associated with aggression and bullying in numerous studies. However, the other dimensions of the triarchic model have been relatively unexplored in samples of adolescents. Thus, we tested for associations between the triarchic dimensions and bullying and cyberbullying behaviors (i.e., proactive, goal-directed, and repetitive aggressive behaviors) in a sample of 580 high school students aged 14 to 19 years. Logistic regression analyses showed that (a) meanness and disinhibition scores were uniquely associated with traditional bullying, whereas only meanness was uniquely associated with cyberbullying; (b) boldness scores moderated the relationship between disinhibition and cyberbullying, such that disinhibition was related to cyberbullying only at low levels of boldness; and (c) these patterns were maintained when accounting for overall levels of conduct problems and were not moderated by the experience of victimization. Our findings suggest that the triarchic model of psychopathy can contribute to an understanding of youth engagement in bullying and cyberbullying.